Pengaruh WCTO dan DER terhadap ROE pada Perusahaan Farmasi di BEI Periode 2014-2018 - Dewi Ratnasari; Ine Mayasari; Endang Hatma Juniwati (Indonesian Journal of Economics and Management, 2021)
The research conducted in this final project aims to know how the influence of Working Capital Turnover and Debt to Equity Ratio toward Return On Equity at the pharmaceutical company which are listed in Indonesia Stock Exchange (IDX) period 2014-2018. Using the purposive sampling method, 7 pharmaceutical companies at IDX period 2014-2018 were selected for use as an sample of this research. The data used in this research is secondary data of the company’s annual financial statements. The data analysis method used is multiple regression analysis using IBM SPSS Statistics 26. The results showed that simultaneously the Working Capital Turnover and Debt to Equity Ratio significantly affected toward Return On Equity with a level of influence gained is 60.2%. Partially, Working Capital Turnover has a negative and significant effect toward Return On Equity as well as Debt to Equity Ratio affecting the negative and significant toward Return On Equity.